The Application Value of Ultrasound Medicine in Surgical Teaching Under the Concept of Precision Surgery - She, Tianyu; Zhao, Yina; Dang, Hongmin; Hu, Qiyi; Tian, Xiaoying; Jing, Na; Qian, Hangyan; Yun, Dan; Gao, Yunlong; Zhao, Xiaoxiao (International Journal of Public Health and Medical Research, 2026)
In the context of the rapid development of precision medicine, precision surgery has gradually become the core development direction of modern surgery, which emphasizes accurate diagnosis, precise localization, minimally invasive operation, real-time monitoring and individualized treatment. With the unique advantages of real-time imaging, non-invasiveness, repeatability, bedside availability and dynamic visualization, ultrasound is highly consistent with the educational needs and practical scenarios of precision surgery. However, traditional surgical teaching is still restricted by static anatomical teaching, insufficient clinical practice opportunities, single teaching mode and lack of interdisciplinary integration, which makes it difficult to systematically cultivate students’ precision thinking, spatial cognitive ability and standardized surgical operation ability. Based on the core connotation and development trend of precision surgery, this paper analyzes the realistic dilemmas and deep-seated problems existing in traditional surgical teaching, and systematically expounds the specific application paths and multi-dimensional application values of ultrasound medicine in surgical teaching from four aspects: visualized anatomical teaching, standardized skill training, interdisciplinary knowledge integration and diversified teaching evaluation. This study confirms that the deep integration of ultrasound medicine into the whole process of surgical teaching can effectively break through the limitations of traditional teaching, significantly improve the intuitiveness, scientificity and effectiveness of surgical teaching, enhance students’ three-dimensional spatial cognition and clinical practical ability, cultivate rigorous precision thinking and interdisciplinary comprehensive competence, and provide a practical and feasible path for medical colleges and universities to cultivate high-quality surgical talents adapting to the development requirements of modern precision surgery.